Paleomagnetism of the Sutton Lake Proterozoic inlier, Ontario, Canada - Schwarz, E. J.; Clark, K. R.; Fujiwara, Y. (Canadian Journal of Earth Sciences, 1982)
Thirty-eight cores were collected from eight sites in the Sutton Lake Proterozoic inlier, which is thought to be an extension of the Circum-Ungava Belt. Six sites from a 100 m thick diabase sill yielded essentially single-component magnetization averaging D = 35°, I = −54°, k = 39,α 95 = 11°. The diabase dips north at 4° and shows only minor alteration (epidote and chlorite). The other two sites were in a fine-grained dark layer within the sill and in a dike. No end points were observed for these sites upon alternating field and thermal demagnetization. The six diabase sites yielded a north pole at 67°E, 3°S, dm = 15, dp = 11. This pole position is similar to that obtained for the youngest volcanic suite (Flaherty Formation) of the Belcher Islands and to that obtained for red beds of the La Grande 4 outlier, suggesting a time-stratigraphic correlation between these units.